2021
DOI: 10.1017/s0021932021000390
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) and body mass index in the BBC Internet Study: prenatal sex steroids and a Trivers–Willard effect on body composition

Abstract: Digit ratio – a putative measure of prenatal sex steroids – may be related to body mass index (BMI). However, reports of correlations between 2D:4D and BMI have yielded mixed results with some studies showing no relationship while others have reported positive associations in men or women only. This study considers associations between self-reported 2D:4D and BMI in a large online survey (i.e. the BBC Internet Study). At the individual level, there was a weak positive association between 2D:4D and BMI in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
3
1
Order By: Relevance
“…On the other hand, Fink et al found that BMI in men (but not in women) is positively related to the digit ratio, but it remains significant only for the left hand 36 . Contrary to this report, Manning et al indicate that 2D:4D is positively associated with BMI, but only in women 37 .…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…On the other hand, Fink et al found that BMI in men (but not in women) is positively related to the digit ratio, but it remains significant only for the left hand 36 . Contrary to this report, Manning et al indicate that 2D:4D is positively associated with BMI, but only in women 37 .…”
Section: Discussioncontrasting
confidence: 97%
“…This is indicated by higher 2D:4D values of the right and left hand in people with obesity than in people with normal body weight. This result is consistent with the reports of many other authors 32 – 34 , 36 , 37 and indicates a new area of activity in the prevention of this disease. At the same time, it seems that the 2D:4D index (especially of the right hand) may be a useful factor in early prediction of the risk of excessive body weight development in humans.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2D:4D R values were associated with higher body weight and BMI in a group of 320 males aged 3-22 [15]. Manning et al finding in adults showed that 2D:4D values (R & L) were positively related to measures of BMI in a very large sample (255,116 participants) [13]. Our findings in children study group are further evidence suggesting the positive relationship between 2D:4D and BMI is influenced prenatally.…”
Section: Plos Onesupporting
confidence: 71%
“…To date few studies have analyzed the 2D:4D digit ratio and body parameters or proportions in adults, with the findings remaining inconclusive [8][9][10][11][12]. However, recently published study conducted by Manning et al showed that 2D:4D is positively related to BMI in a very large sample of adults (255,116 participants) [13]. This indicates the need to investigate whether and how prenatal sex steroid exposure affects developmental processes from prenatal stages through childhood and adolescence to adulthood.…”
Section: Introductionmentioning
confidence: 99%